Nilai Edukasi Candi Jabung Kecamatan Paiton Kabupaten Probolinggo dalam Pembelajaran Sejarah - Eko Muhammad Arif Budiono; Bambang Soepeno; Rully Putri Nirmala P (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2019)
Jabung Temple is a historical heritage temple from Majapahit Kingdom in Probolinggo Regency, which is located in Jabung Candi Village, this temple heritage site is still not maximally used in history learning. this study aims to determine the value of education contained in the temple jabung so that it can help in class learning for students. This study is an analytical / descriptive study of the value of education contained in jabung temples. The research site is the jabung candi village in Paiton sub-district where the temple of jabung stands. The research method is by step 1. heuristics (data collection) through the stages of observation, document study, and interviews 2. Criticism of sources 3. Interpretation through qualitative descriptive and 4. Historiography. The study studied was the value of education contained in the temple in its use in historical learning. Candi Jabung was visited by Maha Raja Hayam Wuruk when traveling east of Java. The journey carried out by the king was followed by the leadership, minister, family and Maha Patih gajah Mada by leading the troops of the parade, the journey also aimed at seeing and uniting the territory of the Majapahit kingdom in the eastern Java region. When you get to Paiton, you can use it as a learning resource in the classroom and as a tangible proof of historical heritage around students. The conclusion is of course there is an educational value contained in this jabung temple in learning history.